National Collegiate Athletic Association Injury Surveillance System: Review of Methods for 2004–2005 Through 2013–2014 Data Collection - Kerr, Zachary Y. (National Athletic Trainers Association, 2014)
BACKGROUND: Since 1982, the National Collegiate Athletic Association has used the Injury Surveillance System (ISS) to collect injury and athlete-exposure data from a representative sample of collegiate institutions and sports. At the start of the 2004–2005 academic year, a Web-based ISS replaced the paper-based platform previously used for reporting injuries and exposures. OBJECTIVE: To describe the methods of the Web-based National Collegiate Athletic Association ISS for data collection as implemented from the 2004–2005 to 2013–2014 academic years. DESCRIPTION: The Web-based ISS monitored National Collegiate Athletic Association–sanctioned practices and competitions, the number of participating student–athletes, and time-loss injuries during the preseason, regular season, and postseason in 25 collegiate sports. Starting in the 2009–2010 academic year, non–time-loss injuries were also tracked. Efforts were made to better integrate ISS data collection into the workflow of collegiate athletic trainers. Data for the 2004–2005 to 2013–2014 academic years are available to researchers through a standardized application process available at the Datalys Center Web site. CONCLUSIONS: As of February 2014, more than 1 dozen data sets have been provided to researchers. The Datalys Center encourages applications for access to the data.